Development of chromatic biosensor for quick bacterial detection based on polyvinyl butyrate-polydiacetylene nonwoven fiber composites. (December 2019) - Vidal, Pablo; Martinez, Misael; Hernandez, Carlos; Adhikari, Ananta Raj; Mao, Yuanbing; Materon, Luis; Lozano, Karen
Graphical abstract: Highlights: Novel results on development of polymeric membranes with biosensing capability. Fast bacterial detection in wound dressing or wearable patches. Flexible, lightweight, and self-powered chromatic bacterial sensors. Abstract: Infections are caused by a wide variety of bacterial pathogens. The severity of the infection can range from imperceptible to potentially fatal. Early bacterial detection is vital to avoid complications. Smart polymer scaffolds have shown promising in biomedical applications. In this work, we prepared polyvinyl butyrate (PVB)/diacetylene (DA) nonwoven fine fibers with diameters ranging from 1.4 to 1.9 µm using the Forcespinning® technique. PVB/DA fibers were subjected to ultraviolet light to polymerize the diacetylene. Polymerization process was analyzed through photo-calorimetry studies; the total heat of cure was quantified to be 4650 J/g. Thermogravimetric analysis showed increased thermal stability of PVB-PDA compared to PVB by about 50 °C. The bio-sensing response to gram positive ( Staphylococcus aureus, Micrococcus luteus, and Corynebacterium amycolatum ) and gram negative ( Escherichia coli and Pseudomonas aeruginosa ) bacteria was investigated. Plates with varying concentration of bacteria were prepared ranging from 10 7 to 1 colony forming units (cfu) per plate. The sensing ability of the chromatic biosensor was observed as soon as 30 min after placing the membranes in the bacteria at 37 °C. Samples exposed to Staphylococcus aureus, Micrococcus luteus, and Escherichia coli responded to the plates with the minimum number of bacteria (6, 3, and 7 cfu/plate, respectively) while the sample exposed to Corynebacterium amycolatum needed more than 6000 cfu/plate to respond within the first 30 min and at all levels within 24 h. The samples exposed to Pseudomonas aeruginosa did not respond within 30 min, a response was observed at 48 h. These flexible membranes show promising potential to be used as scaffolds/bandages to alert patients of potential infections caused by microbial attack before the individual appears symptomatic.